(untitled) (مجلة البحوث الأكاديمية, 2026)
The supply of groundwater of acceptable quality has grown to be a major problem in many parts of the world, especially in locations near coasts that are impacted by seawater incursions, like the one under consideration. The main objective is to determine the groundwater’s hydrogeochemical characterizations and their indicators, as well as its potential for scaling and corrosion. Samples of groundwater were taken from twelve pumping well locations. Major ions determination was the main focus of analyses carried out in accredited labs using standardised procedures. Gibbs diagrams, pipers trilinear, Durov, bar charts, radial plots, Chadha, and stiff diagrams are among the graphical techniques used. For water scaling and corrosion prediction, water stability indices such the Langelier saturation index (LSI), Ryznar stability index (RSI), Puckorius scaling index (PSI), and Aggressive index (AI) are utilized. The hydrochemistry results indicate that all of the water samples are alkaline and indicate that all groundwater samples are neutral to slightly alkaline. In the groundwater cationic dominance pattern, the predominant hydrochemical cations are Na+ > Ca2+ > Mg2+ > K+; whereas the following is the order of the primary anions in groundwater: Cl− > SO42− > HCO3−> CO3−. Based on Piper diagram all of the samples represents Na+- K+-Cl− - SO42− ions revealed an acids HCO3− is the major anion.